The civil rights movement : then and now - Elish, Dan (America: 50 years of change., 2018)
Examines the history of the civil rights movement from it's start in the 1950s with the fight to end segregation through today's battle to stop inequality and violence against minorities. Includes a timeline, a glossary, resources for further information, and color photographs.